Measurement and imaging of infragravity waves in sea ice using InSAR - Andrew R. Mahoney; Dyre O. Dammann; Mark A. Johnson; Hajo Eicken; Franz J. Meyer (Geophysical Research Letters)
Abstract Using short‐temporal baseline interferometric synthetic aperture radar, we capture instantaneous images of a persistent field of infragravity waves propagating through sea ice near Barrow, Alaska, during January 2015. We estimate wave amplitudes to be between 1.2 and 1.8 mm. Curvature of wavefronts is consistent with refraction of waves entering shallow water from a source region north of Barrow. A shallow water wave model indicates that the geometry of the wavefronts is relatively insensitive to the source location, but other evidence suggests the waves may have originated in the North Atlantic, making this perhaps the longest observed propagation path for waves through ice. We also note that steepening of the waves entering shallow water can increase the peak strain by an order of magnitude, suggesting that infragravity waves may play a role in determining the location of the landfast ice edge with respect to water depth.